Perlindungan Hukum Bagi Pekerja Dari Pemutusan Hubungan Kerja Sepihak Akibat Union Busting Analisis Putusan Nomor 229/Pdt.Sus-Phi/2019/Pn.Bdg dan Nomor 436 K/Pdt.Sus-PHI/2020 - Izza, Amalia Sofa; Sulaiman, Abdullah (UIN Syarif Hidayatullah Jakarta, 2024)
Unilateral termination of employment due to union-busting practices is a serious problem in industrial relations in Indonesia. This study analyzes legal protection for workers against unilateral termination of employment due to union busting, referring to the Industrial Relations Court (PHI) Decision Number 229/Pdt.Sus-PHI/2019/PN.Bdg and the Supreme Court Decision Number 436 K/Pdt.Sus-PHI/2020. This study uses a normative juridical method with a case approach, a regulatory approach, and data collection techniques through literature studies. The results of the study indicate that PT. Asmo Indonesia (PT. Denso Manufacturing) is predicted to have carried out union-busting practices by unilaterally terminating the employment of the union chairman without going through the bipartite and tripartite mechanisms by the provisions of the regulations. Although there are indications of violations of the right to associate as regulated in Law Number 21 of 2000, the courts at the PHI and cassation levels do not explicitly summarize the practice of union busting in their legal considerations. Unilateral termination of employment of active workers in trade unions can be charged as an unlawful act. Therefore, it is necessary to strengthen legal protection for workers to prevent discriminatory and repressive actions by employers against freedom of association. In addition, judges in industrial relations cases need to consider more comprehensively the aspects of Human Rights and the principle of justice in every decision related to employment.